Polish National School System in Teschen Silesia in 17th–19th Centuries - Zormanová, Lucie (Biuletyn Historii Wychowania, 2017)
The article begins by introducing the beginnings of schooling in the Teschen Silesia region. It then continues to map the situation after the introduction of compulsory education. The development of schools and the network of schooling institutions are covered, as well as school curricula and the position and competence of teachers in the 17th to 19th centuries. Physical didactic aids of this period are examined, especially textbooks. Finally, the article deals with the issues connected with Germanisation and the national struggle nd awareness of the Polish population in the eschen Silesia region; with the impact of Hasner’s law (Leopold Hasner von Artha) on the development of he national school system in the region; with important figures and organisations that played a ignificant role in the political, cultural and economic changes in society in Teschen Silesia.